ULK1 Signaling in the Liver: Autophagy Dependent and Independent Actions - Rajak, Sangam; Raza, Sana; Sinha, Rohit Anthony (Frontiers in Cell and Developmental Biology, 2022)
Liver is the primary organ for energy metabolism and detoxification in the human body. Not surprisingly, a derangement in liver function leads to several metabolic diseases. Autophagy is a cellular process, which primarily deals with providing molecules for energy production, and maintains cellular health. Autophagy in the liver has been implicated in several hepatic metabolic processes, such as, lipolysis, glycogenolysis, and gluconeogenesis. Autophagy also provides protection against drugs and pathogens. Deregulation of autophagy is associated with the development of non-alcoholic fatty liver disease (NAFLD) acute-liver injury, and cancer. The process of autophagy is synchronized by the action of autophagy family genes or autophagy (Atg) genes that perform key functions at different steps. The uncoordinated-51-like kinases 1 (ULK1) is a proximal kinase member of the Atg family that plays a crucial role in autophagy. Interestingly, ULK1 actions on hepatic cells may also involve some autophagy-independent signaling. In this review, we provide a comprehensive update of ULK1 mediated hepatic action involving lipotoxicity, acute liver injury, cholesterol synthesis, and hepatocellular carcinoma, including both its autophagic and non-autophagic functions.